Identification of a variant associated with early‐onset diabetes in the intron of the insulin gene with exome sequencing. Issue 4 (5th December 2018) - Matsuno, Shohei; Furuta, Hiroto; Kosaka, Kitaro; Doi, Asako; Yorifuji, Tohru; Fukuda, Takuya; Senmaru, Takafumi; Uraki, Shinsuke; Matsutani, Norihiko; Furuta, Machi; Mishima, Hiroyuki; Iwakura, Hiroshi; et al.
Abstract: Whole‐exome sequencing is a new technology. We used it to explore the gene responsible for early‐onset diabetes as a result of impaired insulin secretion in a family. In the INS gene, we identified the heterozygous c.188‐31G>A mutation in the proband – a 43‐year‐old woman. The mutation was also identified in her two daughters with diabetes, but not in her son or her parents, all of whom did not have diabetes. The substitution was located 31 bp proximal to exon 3 in intron 2. It was predicted to create an ectopic splice site leading to inserting 29 nucleotides of intron 2 as an exonic sequence in the transcript. The mutation has been reported in White families, and the present case is the first report in an Asian person. The present results would help in understanding the role of the mutation in developing diabetes. Abstract : We identified the heterozygous c.188‐31G>A mutation in intron 2 of the INS gene, which was associated with early‐onset diabetes as a result of impaired insulin secretion in a family group.